Overt acquired primary hypothyroidism in a ten-year-old girl with perinatally-acquired HIV infection on HAART: A rare association (Bangladesh Journal of Medical Science, 2019)
Overt hypothyroidism is rare in human immunodeficiency virus (HIV)-infected children but can further compromise the child’s quality of life. We report a case of a 10-year-old girl with perinatally-acquired human immunodeficiency virus (HIV) infection who subsequently developed overt acquired primary hypothyroidism. She has been on highly active antiretroviral therapy (HAART) for 9 years but developed goitre 2 years before presentation. Her thyroid gland was diffusely enlarged, firm, freely movable and non-tender. She had no symptoms of hypo- or hyperthyroidism. Physical examination revealed periorbital puffiness. Although her height was 139cm (50th percentile), it was significantly below the target centile range (152.5- 169.5cm). Results of investigations showed very low free T4 and markedly elevated TSH level (31-fold increase above our laboratory reference value). Ultrasonography of the goitre showed multicystic nodules in both lobes. She was commenced on oral levo-thyroxine 100μg once daily.Conclusion: Physicians need to pay more attention to thyroid function in HIV-infected children on HAART, particularly in the presence of linear growth abnormalities.Bangladesh Journal of Medical Science Vol.18(2) 2019 p.411-415